UPCYCLING LIMBAH PLASTIK DENGAN TEKNIK MERENDA (CROCHET) UNTUK PEMBUATAN UPHOLSTERY PADA PRODUK POUF - Lutfiatun Anisa; Apika Nurani Sulistyati (Universitas Mercu Buana, 2023)
The daily use of plastic bags on a large scale has an impact on the increasing amount of plastic bag waste generated. Responding to these problems, the author initiated the utilization of plastic bag waste in the interior field, namely by upcycling plastic bag waste using crochet techniques for making upholstery on pouf products. That way in this design can be formulated a problem of how to process plastic bag waste with crochet techniques into upholstery on pouf products. The purpose of designing this work is to provide alternatives and variations in the processing of plastic bag waste using crochet techniques. This design uses the method of creation proposed by Palgunadi (2007), which includes three processes of planning and making products, namely the exploration process, extraction process, and termination point. The results obtained from this design are that plastic bag waste, especially HDPE types, can be made into plastic fibers because this plastic waste has a medium thickness, but is still strong and very much available. Furthermore, to process plastic waste into plastic fibers, steps are needed such as sorting, cleaning and then cutting plastic bag waste to produce plastic fibers that are ready to be crocheted to produce upholstery poufs that are in accordance with taste.